Covenant Magazine, vol. 36, no. 1 (Spring 2025) - Covenant Theological Seminary (2025)
From the President -- News & Events -- Faculty and Staff News -- Faculty and Alumni Books -- Faculty Profile -- On the Relevance of Creeds and Confessions -- The Holy Spirit and Counseling -- Glorifying the Triune God through Church Planting -- The Word Became Flesh -- Student Profile -- Alumni News